Features of the organization of environmental accounting in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2024)
The successful functioning of any business entity in a complex and rapidly changing environment of the economy is determined by its competitiveness. A competitive entity is an organization that has a high value and demand for its products. Therefore, one of the most important conditions for business development and expansion is considered to be the correct accounting of environmental costs, along with the skillful Organization of the methodology for accounting for production costs and costing.This article reveals the need to study environmental accounting in modern conditions aimed at achieving the ultimate goal of any production in order to reduce the impact of environmental damage caused by industrial enterprises.The purpose of the article is to disclose the methodology of "environmental cost accounting", which reflects the relationship between economic costs and environmental protection costs, which allows ensuring the competitiveness and reliability of products.During the execution of the article, various research methods were used, including the dialectical approach, monographic research and graphic methods.The results and conclusions obtained from the study are highlighted by the degree of influence of companies on the effective organization of environmental activities of organizations, in addition to demonstrating the ability of companies to use rational methods of effective management of economic and environmental costs and the formation of cost.In the scientific article, the definition of the formation of the target cost is formulated, the importance and methods of environmental accounting are studied to determine the competitiveness of products and the impact of production on the environment.Key words. Environmental accounting, environmental costs, calculation of Target costs, management accounting, costing methods.